2006
DOI: 10.1080/00365510600763301
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and superior mesenteric artery resistance index

Abstract: We conclude that intravenous infusion of serotonin increases the resistance index of the superior mesenteric artery (increases downstream resistance) in healthy adult volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…11,12,25 In some studies, RI has been used to assess hemodynamics in the SMA. 21,23 In our study, RI of the SMA and coeliac artery was significantly decreased in triathletes after the race, and this reduced RI suggests mesenteric hyperemia (an increase in blood flow). To our knowledge, this is the first study using RI as a measure of blood flow after prolonged exercise, and therefore, our findings cannot be compared with those from other similar studies.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…11,12,25 In some studies, RI has been used to assess hemodynamics in the SMA. 21,23 In our study, RI of the SMA and coeliac artery was significantly decreased in triathletes after the race, and this reduced RI suggests mesenteric hyperemia (an increase in blood flow). To our knowledge, this is the first study using RI as a measure of blood flow after prolonged exercise, and therefore, our findings cannot be compared with those from other similar studies.…”
Section: Discussionsupporting
confidence: 49%
“…In one other study where RI was used as a measure of blood flow, blood pressure changes were not measured. 21 Other possible mechanisms that may have contributed to a reduced RI are the response to food or fluid intake and variations in other neurotransmitter concentrations, such as 5-hydroxytryptamine. 21 Our study was not designed to measure these parameters as possible mechanisms, and therefore, further studies are required to determine if these mechanisms could explain our observed changes in RI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations